Association of the CYP17 and CYP19 gene polymorphisms in women with polycystic ovary syndrome from Punjab, Pakistan. (4th May 2021) - Munawar Lone, Nasira; Babar, Sana; Sultan, Sikandar; Malik, Saira; Nazeer, Kiran; Riaz, Saba
Abstract: Background: Polycystic ovarian syndrome (PCOS) is considered the most common multifactorial endocrinopathy. Genetic factors play an essential role in the pathogenesis of PCOS. CYP 17 enzyme is responsible for androgenesis, while CYP 19 enzyme works for androgen conversion into aromatic estrogen. Several studies have reported their association with PCOS. This study was aimed to investigate the association of cytochrome P450c17α gene ( CYP17 ) 5′-untranslated region Msp A1/(rs743572) genetic polymorphism and rs2414096 of cytochrome P450 or aromatase ( CYP19 ) gene polymorphism with the susceptibility to PCOS in reproductive-age women from Punjab, Pakistan. Methods: We performed a case-control association study was conducted, including 204 PCOS patients and 100 controls. Genotyping of SNP rs2414096 ( CYP 19 gene) and P450c17α gene ( CYP17 ) 5′-untranslated region Msp A1 was performed on genomic DNA using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Statistical analysis was performed to find out the association of phenotypic and genotypic characters in etiopathology of PCOS. Results: The genotype distribution for CYP 17 5′-UTR MspA1 (TT, TC, CC) revealed that the frequency of genotype TC is significantly higher in PCOS patients (54.9%) vs. controls (OR 4.97, 95% CI 2.75–8.33, p <.001) (12%). The genotype distribution for CYP 19 (GG, GA, AA) showed significantly higher frequency of GA (58.%) and AA (23.5%) in patients as compared to cases (18% and 8%, respectively) (OR 5.49, 95% CI 3.61–8.34, p <.001). Body mass index (BMI), waist, hip, infertility and family history of infertility, PCOS, diabetes, and hypertension were found significantly associated with PCOS. CYP 19 genotypes were found significantly associated with PCOS patients having paraclinical traits of infertility and family history of infertility, while CYP 17 genotypes showed no significant association with any paraclinical traits in PCOS patients. Conclusions: This is the first study on PCOS genotypes from Pakistan and results suggest that CYP 17 5′-UTR MspA1 (rs743572) (genotype TC) and CYP 19 gene (rs2414096) (genotype GA) polymorphisms are significantly associated with susceptibility to PCOS in Pakistani women having the traits of infertility and family history of hypertension.